2017
DOI: 10.1186/s12933-017-0639-y
|View full text |Cite
|
Sign up to set email alerts
|

DPP-4 inhibition with linagliptin ameliorates the progression of premature aging in klotho−/− mice

Abstract: Background:The potential of anti-aging effect of DPP-4 inhibitors is unknown. This study was performed to determine whether linagliptin, a DPP-4 inhibitor, could protect against premature aging in klotho−/− mice. Methods:Klotho−/− mice exhibit multiple phenotypes resembling human premature aging, including extremely shortened life span, cognitive impairment, hippocampal neurodegeneration, hair loss, muscle atrophy, hypoglycemia, etc. To investigate the effect of linagliptin on these aging-related phenotypes, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
1
18
1
1
Order By: Relevance
“…506 In another study, the effects of linagliptin on an animal model of premature aging supported a positive role in preventing muscle loss, based on the larger size of the gastrocnemius muscle in linagliptintreated mice compared with control. 514 Teneligliptin, when compared with a GLP-1R agonist, did not appear to have negative effects on skeletal muscle mass of patients with T2D on dialysis. 511 However, with the recent increase in DPP-4 inhibitor use, there have been reports of this class of medications causing myalgia, extremity pain, muscle weakness, and other musculoskeletal adverse events, such as arthralgia.…”
Section: Incretinsmentioning
confidence: 88%
See 1 more Smart Citation
“…506 In another study, the effects of linagliptin on an animal model of premature aging supported a positive role in preventing muscle loss, based on the larger size of the gastrocnemius muscle in linagliptintreated mice compared with control. 514 Teneligliptin, when compared with a GLP-1R agonist, did not appear to have negative effects on skeletal muscle mass of patients with T2D on dialysis. 511 However, with the recent increase in DPP-4 inhibitor use, there have been reports of this class of medications causing myalgia, extremity pain, muscle weakness, and other musculoskeletal adverse events, such as arthralgia.…”
Section: Incretinsmentioning
confidence: 88%
“…MK‐0626, a DPP‐4 inhibitor, was associated with improvements in mitochondrial biogenesis in skeletal muscle and improvement in exercise capacity of mice who had suffered recent myocardial infarction . In another study, the effects of linagliptin on an animal model of premature aging supported a positive role in preventing muscle loss, based on the larger size of the gastrocnemius muscle in linagliptin‐treated mice compared with control . Teneligliptin, when compared with a GLP‐1R agonist, did not appear to have negative effects on skeletal muscle mass of patients with T2D on dialysis .…”
Section: Drugs and Musclementioning
confidence: 96%
“…The lifespan of klotho −/− mice was prolonged, and their body weight was significantly related to greater kidney weight in the intervention of linagliptin [194]. Although no conclusive evidence has demonstrated that DPP4 inhibition improves diabetic kidney lesions, it may control blood glucose and albuminuria as well as be tolerated in patients with DM and CKD, indicating potential renal benefits [195].…”
Section: Potential Therapeutic Strategy Targeting Accelerated Kidney mentioning
confidence: 99%
“…Moreover, klotho levels are decreased by Ang-2 [ 187 ] and one of the downstream effects of klotho is regulation of NO signaling (Fig. 2 c, f) [ 188 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this was the first study suggesting that the vasculo-protective effects of linagliptin involve modulation of klotho signaling. In addition, a more recent study showed that amelioration of progression of premature aging in klotho knock out mice by linagliptin and these salutary effects were associated with increased bioavailable NO in the cerebral vasculature [ 188 ]. Angiotensin II decreases klotho levels and linagliptin improves Ang II signaling, including downregulation of AT1R [ 35 ].…”
Section: Introductionmentioning
confidence: 99%